Analysis of the Impact of the Shift in Investigative Authority from Sector Police (Polsek) to Resort Police (Polres) on the Law Enforcement Process and Fulfillment of Justice for the Community in the Jurisdiction of the Bangka Belitung Islands Regional Police - Elpiadi; Abdul Rasyid Saliman (Journal of Law, Politic and Humanities, 2024)
The Indonesian National Police (Polri) holds a central role in safeguarding public security, maintaining order, and enforcing the law in Indonesia. The Chief of the National Police's Decision Number: Kep/613/III/2021 introduces a strategic shift of investigative authority from Sector Police (Polsek) to Resort Police (Polres) in designated areas, including within the Bangka Belitung Islands Regional Police jurisdiction. This transformation is designed to optimize preventive functions at the Polsek level. This study employs a normative juridical method combined with an empirical approach through regulatory analysis and interviews with law enforcement officers and community members. The results reveal that this policy shift positively affects the efficiency of case handling while refocusing the Polsek’s role on community security and public service. Several determining factors, such as geographical distance, report volume, and accessibility, significantly influence the selection of Polseks exempt from investigative duties. The findings suggest that delegating investigative tasks to Polres supports better resource allocation for Polri personnel, enhances community-based policing, and ensures preventive measures are implemented effectively. These changes aim to create a more efficient and equitable system of law enforcement that accommodates the specific needs of various local contexts.